Antitoxin CrlA of CrlTA Toxin–Antitoxin System in a Clinical Isolate Pseudomonas aeruginosa Inhibits Lytic Phage Infection - Ni, Muyang; Lin, Jianzhong; Gu, Jiayu; Lin, Shituan; He, Mei; Guo, Yunxue (Frontiers in Microbiology, 2022)
Pseudomonas aeruginosa is an important opportunistic pathogen in cystic fibrosis patients and immunocompromised individuals, and the toxin-antitoxin (TA) system is involved in bacterial virulence and phage resistance. However, the roles of TA systems in P. aeruginosa are relatively less studied and no phage Cro-like regulators were identified as TA components. Here, we identified and characterized a chromosome-encoded prophage Cro-like antitoxin (CrlA) in the clinical isolate P. aeruginosa WK172. CrlA neutralized the toxicity of the toxin CrlA (CrlT) which cleaves mRNA, and they formed a type II TA system. Specifically, crlA and crlT are co-transcribed and their protein products interact with each other directly. The autorepression of CrlA is abolished by CrlT through the formation of the CrlTA complex. Furthermore, crlTA is induced in the stationary phase, and crlA is expressed at higher levels than crlT. The excess CrlA inhibits the infection of lytic Pseudomonas phages. CrlA is widely distributed among Pseudomonas and in other bacterial strains, and may provide anti-phage activities.